Analisis of Financial Literacy Level in Employee Class Students - Kustitik, Kustitik (FKIP Universitas Lampung, 2024)
The purpose of this study was to determine the level of financial literacy of employee class students at Pamulang University. This research is a type of quantitative descriptive research. Respondents of this study are students who take part in the employee class program at Pamulang University, which is the first university in Indonesia to brand itself as a campus with low tuition fees so that it is attractive to many workers from various types of professions. The data collection instrument uses a questionnaire with indicators referring to the provisions of the Financial Services Authority (OJK) regarding “Core Competencies on Financial Literacy fo Adult”, namely: money and transactions, planning and managing finances, risk and reward, and finance landscape. Respondents filled out the questionnaire online using the googleform platform. The sample was obtained using the convenience sampling method, namely by distributing the link to the class WhatsApp group and the participants who filled in were voluntary. A total of 319 questionnaires were completed, but 316 met the criteria. Data were processed using descriptive analysis to answer research questions. The results showed that the level of financial literacy of employee class students at Pamulang University was in the moderate category. For this reason, it is recommended that further research can statistically prove the effect of students' financial literacy on their financial behavior.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.175-181